IMPLEMENTASI BUDAYA RELIGIUS DALAM PENANAMAN ADAB SISWA - Mirza Gulam Ramadhan; Anita Puji Astutik (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
This qualitative research investigates the integral role of religious culture in instilling good manners, often referred to as adab, within the student body of SMK YPM 8 SIDOARJO. The study delves into the symbiotic relationship between educational institutions and religious culture, particularly focusing on how these synergies contribute to shaping students' characters. At SMK YPM 8 SIDOARJO, religious culture is deeply ingrained, encompassing a set of core values denoted as the 5S - smiles, greetings, politeness, and courtesy. Additionally, practices such as memorization, communal prayers, and the daily Dhuhr prayer are fundamental components of this cultural milieu. Through habitualization and the modeling of exemplary behaviors, the religious culture within the school significantly influences the development of adab among students. This influence extends beyond the superficialities of politeness and extends to fundamental values such as discipline, kindness, religiosity, tolerance, and responsibility. The integration of these values into the school's cultural fabric creates a nurturing environment conducive to character formation. The research underscores the critical role played by religious culture in shaping students' characters within the educational context and offers substantial insights for other institutions seeking to enhance their cultural influence on students' moral and behavioral development. By demonstrating the effectiveness of embedding religious values into the educational environment, this study provides valuable guidance for educators and administrators aiming to leverage cultural aspects to foster a well-rounded growth in students, both morally and behaviorally. The findings shed light on the transformative potential of religious culture in molding the future citizens of society, promoting a harmonious and virtuous community.